Field Training Management System using Cloud Computing - Ideas, Rafat; Melhem, Haneen (جامعة بوليتكنك فلسطين - هندسة حاسوب)
Cloud Computing is a general term for anything that involves delivering hosted services over the Internet or a model for delivering information technology services in which resources are retrieved from the Internet through Web-based tools and applications. It eliminates the costs and complexity of buying, configuring, and managing the hardware and software needed to build and deploy applications. Instead, these applications are delivered as a service over the Internet ("cloud”). In this project we will use this environment. In this project we will use this environment and apply it to special case and solve problems that get at universities. The problem is lack opportunities of field training that students face every year, and difficulties in finding training providers so we could use Cloud Computing environment to build a system that can make it easy to find training opportunities and avoid trouble of research and time wasting and cost.
CD , no of pages 102 , 25481, هندسة حاسوب 2/2012 , in the store
Keywords: Cloud Computing; Training Management